Perancangan Smart Home Menggunakan Bluetooth Pada Smartphone Android Dan Arduino - Arif Sigi irawan (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The development of science and technology bring a positive impact in human life which at this time has reached the era of electric. To be able to control the instrument with bluetooth, the smart home control system allows humans to control their home electrical devices such as lights only by using bluetooth commands without moving around to switch on or off a device. When an indoor light user runs the system or turns on the light with Bluetooth singal, the module bluetooth sends the input signal to the microcontroller which is then processed with the output of the microcontroller in the form of voltage to switch the load, the system will function when the HC05 bluetooth module gets singal input in the form of a tap from smart phone that is worth 0 to 9 accumulated on the arduino with a value according to the program uploaded to be output 5 volts to switch / extinguish the lights, HC05 blutooth module is only able to provide digital output signal of 0 to 9 value.